PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA LABORATORIUM KLINIK THAMRIN CABANG PEKANBARU - Dehotman, Khornelis (Eko dan Bisnis: Riau Economic and Business Review, 2018)
The objective of this research is to know the influence of service quality with the indicator of reliability, responsiveness, guarantee, attention and physical proof to patient satisfaction of Thamrin Cab Clinic Laboratory. Pekanbaru. Samples were taken as many as 100 respondents from patients who have performed health checks at the Thamrin Cab Clinic Laboratory. Pekanbaru. Based on the results of the study note that there is influence of service quality on patient satisfaction with regression equation Y = -5.466 + 0.334X1 + 0.246X2 + 0.228X3 + 0.266X4 + 0.209X5. Simultaneously Fcount value is 116.477 with significant level 0.000. Therefore, in both calculations Fcount> Ftable (116.477> 2.31) and the significance level is 0.000 <0.05, it indicates that Ho is rejected or significant, which means independent variable / independent variable (reliability, responsiveness, assurance, empathy, tangible) jointly affect the satisfaction of patient Lab. Thamrin Cab Clinic. Pekanbaru. Partially by using t test obtained free variable that is reliability / reliability with titung 8.705> ttable 1.985, responsiveness / responsiveness with t count 6.002> ttabel 1.985, assurance / assurance with t count 3.234> ttabel 1.985, empathy / attention with tcount 3.376> ttabel 1.985 , tangible / physical proof with thitung 4,318> ttabel 1,985. R Square (R2) of 0.854 or 85.4%, it shows that the dependent variable (patient satisfaction) can be explained by 85.4% by independent variable (reliability, responsiveness, assurance, empathy, tangible) while the remaining 14.6% is influenced by other variables that are not included in this study. Expected to Thamrin Clinic Laboratory Cab. Pekanbaru to be able to make continuous improvement and improve the quality of service to the patient so that able to survive and become patient choice to conduct medical examination